6y-11=19

Simple and best practice solution for 6y-11=19 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6y-11=19 equation:


Simplifying
6y + -11 = 19

Reorder the terms:
-11 + 6y = 19

Solving
-11 + 6y = 19

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '11' to each side of the equation.
-11 + 11 + 6y = 19 + 11

Combine like terms: -11 + 11 = 0
0 + 6y = 19 + 11
6y = 19 + 11

Combine like terms: 19 + 11 = 30
6y = 30

Divide each side by '6'.
y = 5

Simplifying
y = 5

See similar equations:

| 12f-4=2f+9 | | 4x=22-6 | | 5n+8n+4= | | x=96-0.5*(96-0.5*x) | | 7(3x+21)-4(11-3x)=4(4x+1)-14(9-x) | | 6x+-9=-21 | | 5s-6=10 | | A+60+85+2A=235 | | 2e+10=e+8 | | 3n-7=n+5 | | -x^2+6x=-8 | | 5(45y^2+123y+84)=0 | | 3d+1=20+2 | | t^2-26t+160=0 | | x+x+7=74 | | 5x+y=-25 | | e^3x-9=8 | | 9x=41 | | 8x-7x=22 | | ln(3x+5)=12 | | abs(3x-5)=2 | | .2x+9=15 | | 16-a=3a | | 9a+4a-5a= | | -3x+12=4+2x | | 2-8x=6-3x | | z-16=3z | | 7p+3=2p+48 | | 4x(x^2-4)=0 | | ln(x)+ln(4)=2ln(x+1) | | 4a^2-ab-a^2+4ab= | | 0.05x=1.6+0.25x |

Equations solver categories